استعمال قاموس اللغة العربية و فوائده في فهم معانى التراكيب اللغوية في تعليم اللغة العربية من الناحية العملية - Irfandi, Ahmad Muhaimin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Language is a communication tool that can make people work together and interact with each other. Because language is a means of communication, what is more important in learning the language is how we can use the language to communicate daily. For humans in general, language mastery is a remarkable achievement during one’s life. This study intends to know the use of dictionary and the benefits of the use of dictionaries among students in understanding the meaning of the structure of language in learning Arabic, both in class and outside the classroom. Understanding the meaning of language structure equals understanding the meaning of a word contained in Arabic texts. From the analysis of interviews and observations conducted by me and some of my students, the use of Arabic dictionaries is higher when learning Arabic outside the classroom. And the use of the dictionary itself has benefited both directly and indirectly in understanding the meaning of language structure on Arabic Learning in Pondok Pesantren Modern Al-Iman Wonogiri, Central Java